Evaluating the role of inflammatory biomarkers as a diagnostic tool in peri-implantitis - Ayan Saxena; Pavitra Kumar Rastogi; Nand Lal; Umesh Pratap Verma; Rameshwari Singhal; Md. Kaleem Ahmad (Journal of Oral Biology and Craniofacial Research)
Background: Most studies have analyzed the presence of cytokines in Gingival crevicular fluid (GCF) in different periodontal diseases, but very limited studies have been conducted on Peri-implant crevicular fluid (PICF) in peri-implantitis. Aim: The present study was conceptualized to explore the levels of Interleukin (IL)-1β and Interleukin (IL)-6 as a diagnostic marker in peri-implantitis. Materials and methods: A total of 40 patients each having at least one dental implant were enrolled in the study. Clinical parameters were recorded around each implant and tooth nearest to it. Gingival crevicular fluid (GCF)/Peri-implant crevicular fluid (PICF) was collected to evaluate the concentration of IL‐1β and IL‐6. Conservative treatment was performed in peri-implantitis cases, 3 months after treatment their clinical parameters, IL-1β and IL-6 levels were recorded and compared with their pre-treatment values. Results: Clinical parameters like Modified Plaque Index (MPI), Modified Bleeding Index (MBI) and Probing Pocket Depth (PPD) were statistically significantly higher in the peri-implantitis group as compared to the healthy implant group and healthy teeth group. IL-1β and IL-6 levels were also statistically significantly higher in the peri-implantitis group in comparison to healthy implants and healthy teeth group. Conclusion: The study concludes that biomarkers in PICF can be used as a diagnostic tool to supplement the diagnosis of peri-implantitis along with the use of clinical parameters to make an early diagnosis of peri-implantitis possible.